LITERASI DIGITAL SEBAGAI JEMBATAN PENGUATAN PENDIDIKAN KARAKTER DI ERA 5.0 - Mufidatul Husna; Primanita Sholihah Rosmana; Mufidatul Husna; Pani Herlina; Supriatna (STKIP Subang, 2024)
In education, the most important component is character, where character is aframework for developing moral, ethical and emotional values in students. TheSociety 5.0 era is an era where humans will be surrounded by technology.Therefore, digital-based literacy is the key to strengthening character education inthis era. Digital literacy refers to an individual's ability to use, evaluate, and activelyparticipate in digital environments. This article aims to provide insight into the roleof digital literacy in strengthening character education in the Society 5.0 era. Themethod in this research uses literature study. Data collection techniques in thisresearch come from various relevant sources. This research analyzes therelationship between digital literacy and strengthening character education byconsidering aspects such as technological knowledge, digital skills, responsiblebehavior on online media, and ethical awareness in the digital world. The researchresults show that digital literacy can be an effective way to strengthen charactercultivation in the era of society 5.0. Through digital literacy, students can developvalues such as honesty, responsibility, empathy, cooperation and problem solving.Therefore, digital literacy has a role as a bridge to strengthen character educationin the era of society 5.0.